1999
DOI: 10.1046/j.1523-1747.1999.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

FGF Expression Allows Nevus Cells to Survive in Three-Dimensional Collagen Gel Under Conditions that Induce Apoptosis in Normal Human Melanocytes

Abstract: Melanocytes, the pigment forming cells of the skin, form an almost nonproliferating cell population located to the lowermost part of the epidermis. Normally melanocytes are not found higher in the epidermis or in the dermis. Nevi consist of melanocytes with altered growth characteristics and localization. The common pigmented nevus, a benign skin lesion, develops when melanocytes proliferate in the dermo-epidermal junction or in the dermis. Here we report growth characteristics of in vitro cultured normal huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…We showed that either matrix adhesion or exogenous growth factors are sufficient to protect human melanocytes from apoptosis. These data are consistent with previous findings demonstrating that melanocytes are protected from apoptosis when plated on fibronectin, laminin or collagen III (Scott et al, 1997) but not type I collagen gels (Alanko et al, 1999;Alanko and Saksela, 2000). In the absence of adhesion and subsequent activation of AKT, our data demonstrated that B-RAF V600E signaling is sufficient for survival of melanoma cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We showed that either matrix adhesion or exogenous growth factors are sufficient to protect human melanocytes from apoptosis. These data are consistent with previous findings demonstrating that melanocytes are protected from apoptosis when plated on fibronectin, laminin or collagen III (Scott et al, 1997) but not type I collagen gels (Alanko et al, 1999;Alanko and Saksela, 2000). In the absence of adhesion and subsequent activation of AKT, our data demonstrated that B-RAF V600E signaling is sufficient for survival of melanoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…Resistance to apoptosis in melanoma K Boisvert-Adamo and AE Aplin B-RAF knockdown WM793 cells are protected from apoptosis on fibronectin but not collagen Anoikis can result not only from loss of attachment but also from adhesion to an inappropriate matrix. For example, culture of melanocytes in type I collagen gels induces apoptosis (Alanko et al, 1999;Alanko and Saksela, 2000). During the vertical growth phase, melanoma cells invade into the dermis, a matrix composed primarily of type I collagen but also containing fibronectin deposits.…”
Section: Resultsmentioning
confidence: 99%
“…Nevomelanocytes are to be more resist- ent to apoptosis than normal melanocytes. Increased resistance to apoptosis in nevi is likely mediated by the expression of inhibitor of apoptosis proteins [33] and acquisition of survivin expression in melanocytes may contribute to apoptosis resistance in these skin lesions [16].…”
Section: Discussionmentioning
confidence: 99%
“…51,52 The importance of FGF signalling in melanoma has been demonstrated by numerous studies. [53][54][55][56][57][58] Thus, if the interaction between FLRT3 and FGF signalling is conserved in humans, it is possible that mutations in p14ARF promote the activation of the FGF pathway by regulating FLRT3 expression.…”
Section: Discussionmentioning
confidence: 99%